Referential revealed preference theory - Hassan Nosratabadi (Rutgers University, Department of Economics, 2017)
References can influence choice. One of the well-studied cases is when a decoy is added to the menu. However small in magnitude, decoy effect violates the weak axiom of revealed preferences (WARP). In order to explain the small deviation from the classical revealed preference theory, I decompose WARP into independent axioms in order to only remove the ones which are inconsistent with the this effect. This minimal deviation produces the referential revealed preference theory that keeps the strong predictive power offered in the classical theory while explaining the referential effect.
Keywords: D11; D81; 330; Reference-Dependent Choice; Reference Preferences; Decoy Effect; Attraction Effect; WARP Decomposition